Effect of Respiration and Vascular Tone on Heart Rate Variability in Rats - Chizh, Nikolay A. (Problems of Cryobiology and Cryomedicine, 2016)
Basing on findings of a combined study (electrocardiography, pneumotachography, direct sphygmography) the paper discusses the effect of respiration and vascular tone on heart rate variability (HRV) in rats and presents a physiological interpretation of the selected spectral ranges. Studying the HRV in conscious rats showed the lower HF-wave range limit to be not higher than 0.8Â Hz, and the upper one not less than 2.5 Hz;Â under stress this index increased up to 3 Hz. The experiments showed that conscious rats were characterized with the â€˜package-likeâ€™ respiration (from 2 to 15â€“20 s). The respiratory rate in each â€˜packageâ€™ was different, therefore two or more peaks might be recorded at high-frequency spectral range. This fact confirmed the existence of several oscillators-pacemakers of respiratory center. In the anaesthetised rats the vasomotor waves were established to affect the variability of respiratory and heart rates within the range of 0.25â€“0.5 Hz with 0.4 Hz peak. Therefore the lower limit of the average MF waves should not exceed 0.25 Hz. Â Probl Cryobiol Cryomed 2016; 26(3): 260â€“270